The Bacterial Microbiome Associated With Arid Biocrusts and the Biogeochemical Influence of Biocrusts Upon the Underlying Soil - Moreira-Grez, Benjamin; Tam, Kang; Cross, Adam T.; Yong, Jean W. H.; Kumaresan, Deepak; Nevill, Paul; Farrell, Mark; Whiteley, Andrew S. (Frontiers in Microbiology, 2019)
Biocrusts are aggregated crusts that exist on the soil surface of arid environments. They are complex microbial communities comprised of cyanobacteria, lichens, mosses, algae and fungi. Recently, biocrusts have gained significant attention due to their ubiquitous distribution and likely important ecological roles, including soil stabilisation, soil moisture retention, carbon (C) and nitrogen (N) fixation and, thus, as a potential agent of ecosystem engineering in arid environments. Here, we collected three co-occurring types of biocrust (Crust A-C) and their underlying soil from the arid zones within Western Australia. Microbial composition was determined through 16S rRNA gene amplicon sequencing, while the abundance of N-fixing genes was determined using qPCR of nifH genes, and N-cycling processes traced with natural δ15N abundance assays. We determined that the microbial communities of native biocrusts are distinct from those in their underlying soil, where dominant taxa differed according to crust types. Abundance of nifH ranged from 1.4 × 103 to 8.51 × 104, and was highest in Crust A, whilst δ15N revealed that N-fixation was most evident in Crust C (1.73 ± 1.04 ‰). Consequently, depending upon the crust type, biocrusts contained higher concentrations of organic C (two to 50 times), total N (four to 16 times) and available ammonium (two to four times), though this enrichment did not extend to the soils underneath them. These findings demonstrate that biocrust communities are islands of biological activity in an arid landscape, uniquely different from their surrounding and underlying soil. They likely evolve through stages and may be a potential solution to restoring the biological functionality of degraded soils in arid environments, by reintroducing a tolerant native microbiome and improving the nutrient status of the substrate through significant N-fixation capabilities.